ANALISIS PENGARUH TINGKAT INFLASI, TINGKAT SUKU BUNGA, DAN NILAI TUKAR TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA (BEI) PERIODE 2013-2015 - Primavistanti, Daniar; Sutanto, Aftoni (Jurnal Fokus Manajemen Bisnis, 2016)
This research aimed to analyze and test the effect of inflation rates, interest rate and exchange rate  on the stok price index  at the stock exchange in 2013–2015. Independent variable used are inflation, interest rates, and exchange rates. While the dependent variable is the stock price index. The object of this research  is in the market listed  on the stock price index. The  inflation  rates, interest rates,  and  the  exchange  rate that  are  taken  from Indonesian Bank. The  analytical  method used is the classic assumption test and regression test. Based  on  the  survey  result revealed  that in partial  inflation and the exchange  rate does not  significantaly  influence the Stock  Exchange  Composite Index. While the variable interest rate significantly influence the Stock Exchange Composite Index. The test results simultaneosly show variable inflation, interest rates and exchange rates have an influence on the Stock Exchange  Composite Index. The coefficient of determination was 28,3%.